2003
DOI: 10.1034/j.1600-051x.2003.00401.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of chronic periodontitis

Abstract: Over a 26-year period, 25% of the subjects went through adult life with healthy and stable periodontal conditions. The remaining 75% developed slight to moderately progressing periodontal disease with progression rates varying between 0.02 and 0.1 mm/year with a cumulative mean of loss of attachment of 2.44 mm as they approached 60 years of age. The annual mean rate and the mean annualized risk of initial attachment loss were highest between 16 and 34 years of age. Only 20% of the sites continued to lose furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
66
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 20 publications
9
66
2
Order By: Relevance
“…This agrees with the previous analysis of these data (Schätzle et al 2003b) which demonstrated that the effect of gingivitis was in the over 40-year olds and as they approached 60 years of age.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This agrees with the previous analysis of these data (Schätzle et al 2003b) which demonstrated that the effect of gingivitis was in the over 40-year olds and as they approached 60 years of age.…”
Section: Discussionsupporting
confidence: 83%
“…The rate of attachment loss during various stages of adult life was further assessed in a third analysis of the cohort (Schätzle et al 2003b). This analysis revealed that the annual rates and the annualized risks of periodontal attachment loss vary throughout adult life.…”
Section: )mentioning
confidence: 99%
“…In an elderly population (65% of the patients were older than 35 years of age), the risk of developing a periodontal condition is increased. 7,33 This study confirmed GDP-recording behaviour, especially by those GDPs with a positive attitude to systematic periodontal screening, regarding patients' factors like plaque accumulation, periodontal pockets, and oral health compliance. These GDPs also are inclined to register significantly more initial carious lesions, although a reliable screening system for dental caries activity and progression is not available for clinical practice.…”
Section: Discussionsupporting
confidence: 82%
“…For the prevention of further vascular destruction by mediators of inflammation, Schoppet et al 15 hypothesized that vascular system releases OP as a part of the compensatory mechanism. Mean AL loss seen in our study was comparable to the results seen in previous studies by Schätzle et al 16 As far as radiographic changes are concerned, similar results have been obtained, which correlate with the results of past studies. 17 No significant differences were observed in the pattern and quantitative analysis of microbial flora in the two study groups.…”
Section: Discussionsupporting
confidence: 83%